Numerical Simulation of Icing on Nrel 5-MW Reference Offshore Wind Turbine Blades Under Different Icing Conditions - Cao, Hui-qing; Bai, Xu; Ma, Xian-dong; Yin, Qun; Yang, Xiang-yu (China ocean engineering, 2022)
Offshore wind energy resources are operational in cold regions, while offshore wind turbines will face the threat of icing. Therefore, it is necessary to study icing of offshore wind turbines under different icing conditions. In this study, icing sensitivity of offshore wind turbine blades are performed using a combination of FLUENT and FENSAP-ICE software, and the effects of liquid water content (LWC), medium volume diameter (MVD), wind speed and air temperature on blade icing shape are analyzed by two types of ice, namely rime ice and glaze ice. The results show that the increase of LWC and MVD will increase the amount of ice that forms on the blade surface for either glaze ice or rime ice, and an increase of MVD will expand the adhesion surface between ice and blade. Before reaching the rated wind speed of 11.4 m/s, it does not directly affect the icing shape. However, after reaching the rated wind speed, the attack angle of the incoming flow decreases obviously, and the amount of ice increases markedly. When the ambient air temperature meets the icing conditions of glaze ice (i.e., −5°C to 0°C), the lower the temperature, the more glaze ice freezes, whereas air temperature has no impact on the icing of rime ice. Compared with onshore wind turbines, offshore wind turbines might face extreme meteorological conditions, and the wind speed has no impact on the amount of ice that forms on the blade surface for most wind speeds